Poligami dalam Teori Hukum dan Mazhab Fikih: Studi Perbandingan Indonesia dan Tunisia - Willy Zulfan; Sukiati Sukiati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Polygamy is one of the most problematic issues in Islamic family law because it lies at the intersection of normative texts, interpretations by fiqh schools, state policy, and demands for substantive justice. This article compares the regulations on polygamy in Indonesia and Tunisia by situating them within the framework of Islamic legal theory, fiqh schools, maqashid al-shari‘ah, and modern family law policy. This study employs a qualitative-normative method based on a literature review of regulations, court decisions, legal documents, fiqh literature, and recent scholarly research from 2020 onward. The findings indicate that Indonesia adopts an “open monogamy” model, wherein polygamy remains permissible but is restricted through court authorization, the wife’s consent, financial capacity, and guarantees of justice. Tunisia has adopted a stricter model an absolute ban through the Code of Personal Status, which criminalizes the practice of polygamy. This difference reflects two strategies for the reform of Islamic law, Indonesia’s is more accommodative yet restrictive, while Tunisia’s is more prohibitive and radical. This article argues that both models stem from the concept of maslahat (public interest), but differ in their interpretation of the best way to protect women, children, and family stability. In practice, the effectiveness of the law is determined not only by the wording of the norms but also by the state’s capacity to enforce the rules consistently and fairly.